Epidemiological investigation and ultrasonic diagnosis of developmental dysplasia of the hip in Chinese infants: A large multi-center cohort study. Issue 2 (14th January 2022) - Xu, Na; Xia, Bei; Tao, Hongwei; Sun, Ke; Liu, Qinghua; Chen, Wenjuan; Wang, Dan; Gao, Hong; Guo, Yan; Liu, Yan; Gao, Jun; Teng, Jianbo; et al.
Abstract : Abstract: Developmental dysplasia of the hip (DDH) is common among Chinese infants, but a lack of large-scale, multi-center epidemiological studies has made it difficult to characterize the risk factors associated with this disease.This multi-center cohort study included 19, 833 Chinese infants aged 14 days to 6 months. A multi-center ultrasound protocol was used to diagnose hip abnormalities, and epidemiological data of the infants were collected through questionnaires. Categorical variables were expressed as percentages and compared using χ 2 test. Multivariate analysis was performed through logistic regression. Of 19, 833 infants, 345 had DDH (1.7%). DDH incidence was higher in female infants (n = 279) than in male infants (n = 66) (χ 2 = 95.89, P < .05), and there were more left hip cases (n = 149) than right hip cases (n = 79) (χ 2 = 12.49, P < .05). DDH incidence was statistically different amongst different age groups in months (χ 2 = 451.71, P < .05), and it gradually decreased with age ( P < .05). The prevalence of a positive DDH family history, breech presentation, oligohydramnios, swaddling style, and other musculoskeletal deformities was higher in the positive group than in the negative group (all P < .05). No significant differences were found in terms of delivery by cesarean section, multiple births, or premature birth between both groups. Family history, breech presentation, oligohydramnios, musculoskeletal deformities, and female sex are high-risk factors for DDH in Chinese infants. The incidence of DDH gradually decreases with age. The results of this study provide evidence for the epidemiology of infant DDH in China.